Socio-economic inequalities in health: a review of the Greek evidence - Νικολάου Αγγελική; Οικονόμου Αθηνά (SPOUDAI Journal of Economics and Business, 2005)
The socioeconomic status effects on individual health state are increasingly recognised in ac ademic literature. This survey reviews the existing theoretical and empirical findings in Greece, the indicators applied and the methodological problems encountered in the existing literature. Thus, the study aims at informing both the researcher and the policy maker about the state of knowledge regarding the effects of socioeconomic and occupational status on health. l;' JEL Classification Code: 11